UESTION 1 1. Given: (i) \( A=60^{\circ} \) and \( B=30^{\circ} \) (ii) \( A=110^{\circ} \) and \( B=50^{\circ} \) (iii) \( A=225^{\circ} \) and \( B=135^{\circ} \) Use a calculator to evaluate each of the following: \( \begin{array}{l}\text { (a) } \cos (A-B) \\ \text { (b) } \cos A-\cos B \\ \text { (c) } \cos A \cdot \cos B+\sin A \cdot \sin B \\ 2\end{array} \) Compare the values of \( \cos (A-B) \) with the values of \( \cos A-\cos B \) and \( \cos A \cdot \cos B+\sin A \cdot \sin B \) Using your \( \operatorname{comparison} \) in Question \( 1.2 \cdot \), what general \( \operatorname{conclusion~can~be~made~regarding~} \) \( \cos (A-B), \cos A-\cos B \) and \( \cos A \cdot \cos B+\sin A \cdot \sin B \) for any values of \( A \) and \( B \) ?
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
Let’s tackle each angle step by step! For \( A = 60^\circ \) and \( B = 30^\circ \): (a) \( \cos(60^\circ - 30^\circ) = \cos(30^\circ) \approx 0.866 \). (b) \( \cos(60^\circ) - \cos(30^\circ) = 0.5 - 0.866 \approx -0.366 \). (c) \( \cos(60^\circ) \cdot \cos(30^\circ) + \sin(60^\circ) \cdot \sin(30^\circ) = (0.5 \cdot 0.866) + (0.866 \cdot 0.5) = 0.433 + 0.433 = 0.866 \). For \( A = 110^\circ \) and \( B = 50^\circ \): (a) \( \cos(110^\circ - 50^\circ) = \cos(60^\circ) = 0.5 \). (b) \( \cos(110^\circ) - \cos(50^\circ) \approx -0.342 - 0.643 \approx -0.985 \). (c) \( \cos(110^\circ) \cdot \cos(50^\circ) + \sin(110^\circ) \cdot \sin(50^\circ) \approx (-0.342 \cdot 0.643) + (0.940 \cdot 0.766) \approx -0.220 + 0.719 \approx 0.499 \). For \( A = 225^\circ \) and \( B = 135^\circ \): (a) \( \cos(225^\circ - 135^\circ) = \cos(90^\circ) = 0 \). (b) \( \cos(225^\circ) - \cos(135^\circ) \approx -0.707 - (-0.707) = 0 \). (c) \( \cos(225^\circ) \cdot \cos(135^\circ) + \sin(225^\circ) \cdot \sin(135^\circ) \approx (-0.707 \cdot -0.707) + (-0.707 \cdot 0.707) = 0.5 - 0.5 = 0 \). Now, comparing the values we notice a pattern! For the calculated values of \( \cos(A-B) \), \( \cos A - \cos B \), and \( \cos A \cdot \cos B + \sin A \cdot \sin B \): 1. \( \cos(A-B) \) consistently equals \( \cos A \cdot \cos B + \sin A \cdot \sin B \). 2. The \( \cos A - \cos B \) can differ significantly, indicating it may not adhere to a predictable relationship with the other two expressions. Thus, we can conclude: 1. \( \cos(A-B) \) is equal to \( \cos A \cdot \cos B + \sin A \cdot \sin B \) for any angle \( A \) and \( B \). 2. \( \cos A - \cos B \) generally takes on values independent of this relationship and can be greater than, less than, or equal to zero. In essence, embracing trigonometric identities can clear the fog of confusion!